Fundamentals of Entrepreneurship (ENT300) : Patata Deliciosa / Dyg Atiqah Syahirah Awg Adam ... [et al.] - Awg Adam, Dyg Atiqah Syahirah; Ibrahim, Nur Aina; Awg Kederi, Dyg Nursyifa Fazrin; Mohd Zollani, Farah Athirah; Adenan, Abdul Muzhaffar; Syamsul Amri, Mohammad Amir Hakimi (2019)
Before starting up our business which is called Patata Deliciosa, the needs and wants of the customer must be identify. This is to help generate ideas or ways to gain the interest of the customer. After identifying the needs of customer, the next step is to scan the environment and evaluating one self and community. Under environment there are population structure, income and taste, media and internet, new government ruling and industrial linkage.while for one self mostly focus on experience,knowledge and skills,financial network and interest